The role of microRNAs in hepatocellular carcinoma: Therapeutic targeting of tumor suppressor and oncogenic genes - Farsi, Nasim Rahimi; Naghipour, Bahman; Shahabi, Parviz; Safaralizadeh, Reza; Hajiasgharzadeh, Khalil; Dastmalchi, Narges; Alipour, Mohammad Reza (Clinical and Experimental Hepatology, 2023)
Hepatocellular carcinoma (HCC) is a severe malignant liver cancer with a poor prognosis and a high mortality rate. This carcinoma is a multistage process that begins with chronic hepatitis and progresses to cirrhosis, dysplastic nodules, and eventually HCC. However, the exact molecular etiology remains unclear. MicroRNAs (miRs) are small non-coding RNAs that modulate the expression of numerous genes. These molecules have become significant participants in several functions, including cell proliferation, differentiation, development, and tumorrelated properties. They have a pivotal role in carcinogenesis as oncogenes or tumor suppressor genes. Furthermore, some investigations have shown that particular miRs might be used as predictive or diagnostic markers and therapeutic targets in HCC therapy. This review study summarizes the current level of knowledge on the role of miRs in the initiation and progression of HCC.